The Birmingham blood pressure school study. Issue 696 (October 1983) - De Giovanni, J. V.; Pentecost, B. L.; Beevers, D. G.; Beevers, M.; Jackson, S. H.; Bannan, L. T.; Osbourne, V. L.; Mathews, K.
Abstract : Four-hundred and twenty-eight school leavers of 3 ethnic groups (white, black and Asian) were screened for blood pressure, resting pulse rate and general anthropometric characteristics. Asian pupils were both shorter and lighter than the other two groups whilst black males were heavier and taller. There was no significant difference in the mean systolic or diastolic blood pressure between the 3 groups, although the black pupils had a stronger family history of hypertension, particularly on the mother's side. These observations differ in some respects from other ethnic blood pressure studies and establish values for the local population.